2015
DOI: 10.1159/000430852
|View full text |Cite
|
Sign up to set email alerts
|

Updated Evidence on the Mechanisms of Resistance to ALK Inhibitors and Strategies to Overcome Such Resistance: Clinical and Preclinical Data

Abstract: Anaplastic lymphoma kinase(ALK) rearrangement is one of the oncogenes in non-small cell lung cancer (NSCLC) identified in 2007. The PROFILE trials demonstrated that patients with ALK-rearranged NSCLC can be successfully treated with crizotinib, and that crizotinib is superior to chemotherapy in both first- and second-line settings. Furthermore, next-generation ALK inhibitors, such as alectinib and ceritinib, have been shown to harbor excellent efficacy for NSCLC patients with ALK rearrangement. However, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 56 publications
0
48
0
2
Order By: Relevance
“…Mechanisms responsible for resistance to crizotinib may be due to acquired ALK gene mutations, and activation of other signaling bypass pathway [24,25]. It also has been shown that multiple mechanisms of resistances may occur in the same ALK resistant tumor [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms responsible for resistance to crizotinib may be due to acquired ALK gene mutations, and activation of other signaling bypass pathway [24,25]. It also has been shown that multiple mechanisms of resistances may occur in the same ALK resistant tumor [26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…The last type of ALK gene mutation is point mutation. Secondary resistance is an acquired mechanism after the tumor has been exposed to an ALK inhibitor and most types of resistance are caused by mutations in the target ALK gene, resulting in an inability to inhibit the encoded tyrosine kinase . The first drug resistance point mutations identified were C1156Y and L1196M .…”
Section: The Alk Genementioning
confidence: 99%
“…ALK-dependent mechanisms of resistance, observed in approximately 30% of patients, include the acquisition of secondary mutations in ALK that interfere with crizotinib binding and/or amplification of the ALK fusion gene. More than 10 secondary mutations in ALK have been associated with crizotinib resistance in patients, with the most common being L1196M and G1269A (4,5). The central nervous system (CNS) is the first site of progression in approximately 50% of patients (6,7), suggesting inadequate penetration into the CNS by crizotinib (i.e., pharmacologic failure) as the primary cause of resistance in these patients.…”
Section: Introductionmentioning
confidence: 99%